ANALISIS PERFORMA FOAM PADA GUDANG PKP-PK DI BANDAR UDARA INTERNASIONAL KUALANAMU - Ryan Khrisna; Supri Supri; Gilang Trio Putra (MANAJEMEN, 2025)
This study aims to analyze the performance of firefighting foam stored in the ARFF warehouse at Kualanamu International Airport. Foam is the primary extinguishing agent used in airport firefighting operations, especially for incidents involving flammable liquids. A decline in foam quality can directly affect firefighting effectiveness. This research employs a qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and document analysis. The findings reveal that major factors contributing to foam degradation include unstable room temperatures, direct exposure to sunlight, and improper storage practices, such as mixing foam with other equipment. Additionally, budget constraints remain a key obstacle to constructing a dedicated foam storage facility. These results highlight the importance of proper foam storage in compliance with regulations and the need for adequate infrastructure to maintain foam effectiveness in emergency situations.